TC4 cladding alloy material with large thickness size, preparation method and application thereof

By preparing TC4 cladding alloy material containing tungsten carbide and yttrium oxide, and combining it with laser cladding technology, the problems of insufficient performance and increased thickness of Ti-6Al-4V alloy under friction and wear conditions were solved, achieving high hardness and wear resistance of thick cladding and extending service life.

CN118256909BActive Publication Date: 2026-11-06JIANGSU UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410358756.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2026-11-06
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

Existing Ti-6Al-4V alloys have high friction coefficients, low hardness, and poor wear resistance under friction and wear conditions, which limits their service life. Furthermore, laser cladding technology is prone to porosity and crack defects when increasing the thickness.

Method used

A coating alloy material containing 5-10% tungsten carbide powder, 1-4% yttrium oxide powder and the balance TC4 alloy powder is used. The coating alloy powder is prepared by vacuum induction melting gas atomization and then laser cladding is performed on the surface of titanium alloy. The laser cladding parameters are controlled to achieve the preparation of a thick coating.

Benefits of technology

The preparation of thick coatings has been achieved, which have good toughness, wear resistance and high hardness, reduce cracking tendency, extend the service life of titanium alloys and expand the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118256909B_ABST
    Figure CN118256909B_ABST
Patent Text Reader

Abstract

The present application relates to alloy surface engineering technical field, specifically relates to TC4 cladding alloy material with large thickness size and its preparation method and application, the cladding alloy material is characterized in to include the following 100% weight percentage material: 5-10% tungsten carbide powder, 1-4% yttrium oxide powder, the balance is TC4 alloy powder, after being weighed according to the proportion, ball milling is carried out, and the cladding alloy powder is prepared by vacuum induction melting gas atomization after ball milling;The cladding alloy powder is put into the powder feeder and is carried out laser cladding on the titanium alloy surface, and then the cladding with large thickness size is obtained on the titanium alloy surface;The cladding alloy material of the present application is used as cladding material, which can achieve the cladding with block accumulation thickness on the titanium alloy surface, and the cladding with large thickness still has good toughness, wear resistance, high hardness and thermal stability and other excellent properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy surface engineering technology, specifically to TC4 coated alloy materials capable of producing large thicknesses, their preparation methods, and applications. Background Technology

[0002] Ti-6Al-4V (TC4) alloys possess good strength, plasticity, toughness, corrosion resistance, and weldability, making them widely used in aerospace, marine equipment, chemical industry, and biomedical devices. However, their high coefficient of friction, relatively low hardness, and poor wear resistance limit their service life under friction and wear conditions. Due to the high intrinsic value, complex manufacturing process, high manufacturing cost, and long production cycle of these alloy components, they possess high added value and remanufacturing value. To meet the needs of sustainable and green remanufacturing development, laser cladding technology is currently widely used for surface engineering of titanium alloys.

[0003] Laser cladding, also known as laser bonding or laser coating, involves adding a cladding material to the surface of a substrate and using a high-energy-density laser beam as a heat source to fuse the cladding material and a thin layer on the substrate surface together, thus forming a metallurgically bonded cladding layer. Typically, the cladding layer thickness is approximately 0.2-3.5 mm. However, it is important to note that as the cladding layer thickness increases, more defects appear, such as porosity and cracks. Increased porosity and cracks can lead to cracking of the cladding layer. How to effectively balance the cladding layer thickness and cracking problem is the technical problem that this invention aims to solve. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a TC4 cladding alloy material capable of producing large thicknesses, along with its preparation method and applications. Using the cladding alloy material of this invention as a cladding material, a thickness of at least 3 mm can be achieved on the surface of titanium alloys, with thicknesses exceeding 10 mm. This allows the thick cladding to retain excellent properties such as good toughness, wear resistance, high hardness, and thermal stability.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solution:

[0006] TC4 cladding alloy materials with large thicknesses can be produced, comprising the following 100% by weight of materials: 5-10% tungsten carbide powder, 1-4% yttrium oxide powder, and the balance being TC4 alloy powder.

[0007] Furthermore, the tungsten carbide powder has a particle size of 15-53 μm, the yttrium oxide powder has a particle size of 10-50 μm, and the TC4 alloy powder has a particle size of 53-150 μm.

[0008] The preparation method of the above-mentioned coated alloy material includes the following steps: weighing the above-mentioned materials according to the proportion and then ball milling them, and then atomizing them with vacuum induction melting gas to obtain coated alloy powder.

[0009] Furthermore, the ball mill operates at a speed of 100-300 rpm and a milling time of 8-12 hours. During milling, the grinding balls and the material are in equal mass ratio, and the milling is performed by alternating forward and reverse rotation, changing direction every 5-20 minutes.

[0010] Furthermore, the process of vacuum induction melting gas atomization is as follows: the vacuum degree is no greater than 5 × 10⁻⁶. -2 Under Pa conditions, the ball-milled material is heated to 1750-1850℃ and held for 20-30 minutes. During the heating and holding process, electromagnetic stirring is performed to form a molten liquid. The molten liquid is then atomized into powder under an atomizing gas pressure of 3-7 MPa. After cooling for 30-60 minutes, coated alloy powder is obtained in a powder collection tank and sieved to obtain coated alloy powder with a particle size of 53-75 μm.

[0011] The above-mentioned applications of coated alloy materials capable of producing large thicknesses include the following processing methods:

[0012] S1. Pre-treat the surface of the titanium alloy to remove the surface oxide film and impurities;

[0013] S2. The above-mentioned coating alloy powder is fed into the powder feeder to perform laser cladding on the surface of the titanium alloy, thereby obtaining a coating with a large thickness on the surface of the titanium alloy, with a coating thickness of at least 3 mm.

[0014] The laser cladding process parameters are as follows: laser power of 1.5-3.5kW, spot diameter of 3-5mm, defocusing amount of 15-30mm, scanning speed of 5-10mm / s, overlap rate of 30-50%, and powder feeding rate of 20-50g / min.

[0015] Furthermore, argon gas with a purity of at least 4N is used for protection, with a carrier gas flow rate of 1.5L / min, and laser cladding is performed when the oxygen content in the inert gas chamber is below 100ppm.

[0016] Beneficial technical effects:

[0017] The cladding alloy material of this invention has a simple formulation containing only 1-4 wt% Y₂O₃, 5-10 wt% WC, and the balance TC₄. It is formed into a powder cladding alloy material through vacuum melting and gas atomization, used to repair the surface of titanium alloys. By reducing the content of the easily crack-causing WC strengthening phase, the substrate and cladding bond better after laser cladding, reducing the tendency to crack. No other anti-cracking functional materials are needed. While ensuring crack resistance, this invention enables the preparation of thick cladding layers using the aforementioned cladding alloy material, improving hardness and wear resistance while minimizing the possibility of cladding cracking, extending the service life of titanium alloys, improving their operational reliability, and expanding their application range. Attached Figure Description

[0018] Figure 1 The macroscopic morphology of the cladding layer in the embodiments of the present invention is shown in Figure 1. (a) The cladding layer containing 0% Y2O3 in Comparative Example 1 is shown in Figure 2. (b) The cladding layer containing 1% Y2O3 in Example 1 is shown in Figure 3. (c) The cladding layer containing 1% Y2O3 in Example 2 is shown in Figure 4. (d) The cladding layer containing 3.5% Y2O3 in Example 5 is shown in Figure 6.

[0019] Figure 2 Microhardness diagrams of the cladding layers in Comparative Example 1, Example 1, and Example 3;

[0020] Figure 3 The friction coefficient curves of the cladding layer in Comparative Example 1, Example 1, and Example 3 are shown. Detailed Implementation

[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0022] Unless otherwise specifically stated, the numerical values ​​set forth in these embodiments do not limit the scope of the invention. Techniques and methods known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques and methods should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values.

[0023] Furthermore, it should be noted that the use of terms such as "first" and "second" to specify the added catalyst and the filtrate after the reaction is merely for the purpose of distinguishing the catalyst used in each reaction step and the filtrate produced. Unless otherwise stated, the above terms have no special meaning and therefore should not be construed as limiting the scope of protection of this invention.

[0024] Experimental methods not specified in the following examples are generally performed according to national standards; if there is no corresponding national standard, they are performed according to general standard requirements or general methods.

[0025] Example 1

[0026] TC4 clad alloy materials with large thicknesses can be produced, comprising the following 100% by weight of materials: 10% WC powder, 1% Y2O3 powder, and the balance 89% TC4 alloy powder; wherein the particle size of WC powder is 15-53μm, the particle size of Y2O3 powder is 10-50μm, and the particle size of TC4 alloy powder is 53-150μm.

[0027] The preparation method of the above-mentioned coated alloy material includes the following steps: The material powder of the above proportion is mixed using an XQM-2 planetary ball mill, with an equal mass ratio of grinding balls to material, a ball milling speed of 300 rpm, and a ball milling time of 12 hours. Alternating forward and reverse rotation is used, changing the direction every 10 minutes to obtain the ball-milled mixture powder. The obtained mixture powder is placed in a water-cooled copper crucible in the melting chamber of a vacuum induction melting gas atomization device, and then subjected to a vacuum of 5 × 10⁻⁶. -2 Heating to 1800℃ under Pa conditions and holding for 30 min, with electromagnetic stirring during heating and holding to obtain a melt; then atomizing the melt into powder at an atomizing gas pressure of 6 MPa, and cooling for 60 min to obtain the above-mentioned coated alloy powder in a powder collection tank, and sieving using a vibrating screener to select coated alloy powder with a particle size of 53-75 μm; throughout the powder preparation process, the melting chamber, atomizing chamber and powder collection tank of the vacuum induction melting gas atomization equipment are respectively filled with argon gas with a mass purity greater than 99.99% for protection.

[0028] Application methods for producing TC4 coated alloy materials with large thicknesses include the following processing methods:

[0029] S1. Using TC4 alloy as the substrate, pre-treat a TC4 alloy plate with dimensions of 100mm×100mm×15mm: first, polish the TC4 substrate with 400-grit sandpaper for 10 minutes, then clean it with a 95% ethanol solution for 5 minutes, and dry it with a hair dryer to remove oil stains and impurities adhering to its surface and the oxide film on the alloy surface, so as to achieve a clean and flat surface to be clad.

[0030] Before the experiment, the 53-75μm coated alloy powder prepared above was placed in a vacuum drying oven and dried at a temperature of 130℃ for 3 hours.

[0031] S2. The 53-75μm cladding alloy powder prepared above was fed into the four-channel synchronous coaxial powder feeder of the YLS-4000 fiber laser to perform laser cladding on the titanium alloy surface. The laser power used for laser cladding was 2.5kW, the spot diameter was 3mm, the defocusing amount was 15mm, the scanning speed was 5mm / s, the overlap rate was 40%, the powder feeding rate was 30g / min, the protective gas for laser cladding was argon, and the gas flow rate was 1.5L / min. When the oxygen content in the inert gas chamber reached 80ppm, the laser cladding test was carried out. The cladding thickness obtained in this case was 3mm.

[0032] Example 2

[0033] TC4 clad alloy materials with large thicknesses can be produced, comprising the following 100% by weight of materials: 10% WC powder, 1% Y2O3 powder, and the balance 89% TC4 alloy powder; wherein the particle size of WC powder is 15-53μm, the particle size of Y2O3 powder is 10-50μm, and the particle size of TC4 alloy powder is 53-150μm.

[0034] The preparation method of the above-mentioned coated alloy material includes the following steps: The material powder of the above proportion is mixed using an XQM-2 planetary ball mill, with an equal mass ratio of grinding balls to material, a ball milling speed of 300 rpm, and a ball milling time of 12 hours. Alternating forward and reverse rotation is used, changing the direction every 10 minutes to obtain the ball-milled mixture powder. The obtained mixture powder is placed in a water-cooled copper crucible in the melting chamber of a vacuum induction melting gas atomization device, and then subjected to a vacuum of 5 × 10⁻⁶. -2 Heating to 1800℃ under Pa conditions and holding for 30 min, with electromagnetic stirring during heating and holding to obtain a melt; then atomizing the melt into powder at an atomizing gas pressure of 6 MPa, and cooling for 60 min to obtain the above-mentioned coated alloy powder in a powder collection tank, and sieving using a vibrating screener to select coated alloy powder with a particle size of 53-75 μm; throughout the powder preparation process, the melting chamber, atomizing chamber and powder collection tank of the vacuum induction melting gas atomization equipment are respectively filled with argon gas with a mass purity greater than 99.99% for protection.

[0035] Application methods for producing TC4 coated alloy materials with large thicknesses include the following processing methods:

[0036] S1. Using TC4 alloy as the substrate, pre-treat a TC4 alloy plate with dimensions of 100mm×100mm×15mm: first, polish the TC4 substrate with 400-grit sandpaper for 10 minutes, then clean it with a 95% ethanol solution for 5 minutes, and dry it with a hair dryer to remove oil stains and impurities adhering to its surface and the oxide film on the alloy surface, so as to achieve a clean and flat surface to be clad.

[0037] Before the experiment, the 53-75μm coated alloy powder prepared above was placed in a vacuum drying oven and dried at a temperature of 130℃ for 3 hours.

[0038] S2. The 53-75μm cladding alloy powder prepared above was fed into the four-channel synchronous coaxial powder feeder of the YLS-4000 fiber laser to perform laser cladding on the titanium alloy surface. The laser power used for laser cladding was 2.5kW, the spot diameter was 3mm, the defocusing amount was 15mm, the scanning speed was 8mm / s, the overlap rate was 50%, the powder feeding rate was 40g / min, the protective gas for laser cladding was argon, and the gas flow rate was 1.5L / min. When the oxygen content in the inert gas chamber reached 80ppm, laser cladding was performed. Finally, a thick cladding layer was obtained on the titanium alloy surface. In this case, the cladding thickness was 11mm.

[0039] Example 3

[0040] TC4 clad alloy materials with large thicknesses can be produced, comprising the following 100% by weight percentages of materials: 7.5% WC powder, 3.5% Y2O3 powder, and the balance 89% TC4 alloy powder; wherein the particle size of WC powder is 15-53μm, the particle size of Y2O3 powder is 10-50μm, and the particle size of TC4 alloy powder is 53-150μm.

[0041] The preparation method of the above-mentioned coated alloy material includes the following steps: The material powder of the above proportion is mixed using an XQM-2 planetary ball mill, with an equal mass ratio of grinding balls to material, a ball milling speed of 200 rpm, and a ball milling time of 12 hours. Alternating forward and reverse rotation is used, changing the direction every 5 minutes to obtain the ball-milled mixture powder. The obtained mixture powder is placed in a water-cooled copper crucible in the melting chamber of a vacuum induction melting gas atomization device, and then subjected to a vacuum of 5 × 10⁻⁶. -2Heating to 1850℃ under Pa conditions and holding for 30 min, with electromagnetic stirring during heating and holding to obtain a melt; then atomizing the melt into powder under an atomizing gas pressure of 7 MPa, and cooling for 60 min to obtain the above-mentioned coated alloy powder in a powder collection tank, and sieving using a vibrating screener to select coated alloy powder with a particle size of 53-75 μm; throughout the powder preparation process, the melting chamber, atomizing chamber and powder collection tank of the vacuum induction melting gas atomization equipment are respectively filled with argon gas with a mass purity greater than 99.99% for protection.

[0042] Application methods for producing TC4 coated alloy materials with large thicknesses include the following processing methods:

[0043] S1. Using TC4 alloy as the substrate, pre-treat a TC4 alloy plate with dimensions of 100mm×100mm×15mm: first, polish the TC4 substrate with 400-grit sandpaper for 10 minutes, then clean it with a 95% ethanol solution for 5 minutes, and dry it with a hair dryer to remove oil stains and impurities adhering to its surface and the oxide film on the alloy surface, so as to achieve a clean and flat surface to be clad.

[0044] Before the experiment, the 53-75μm coated alloy powder prepared above was placed in a vacuum drying oven and dried at a temperature of 130℃ for 3 hours.

[0045] S2. The 53-75μm cladding alloy powder prepared above was fed into the four-channel synchronous coaxial powder feeder of the YLS-4000 fiber laser to perform laser cladding on the titanium alloy surface. The laser power used for laser cladding was 3kW, the spot diameter was 3mm, the defocusing amount was 20mm, the scanning speed was 10mm / s, the overlap rate was 50%, the powder feeding rate was 50g / min, the protective gas for laser cladding was argon, and the gas flow rate was 1.5L / min. When the oxygen content in the inert gas chamber reached 80ppm, laser cladding was performed. Finally, a thick cladding layer was obtained on the titanium alloy surface. In this case, the cladding thickness was 13mm.

[0046] Comparative Example 1

[0047] The formulation of the cladding alloy powder in this case is: 10% WC powder and 90% TC4 alloy powder. The preparation of the cladding alloy powder is the same as in Example 1. The laser cladding application process on the titanium alloy surface is the same as in Example 1. The cladding thickness is the same as in Example 1.

[0048] Test case

[0049] Performance tests were conducted on the above embodiments and comparative examples, including interstitial hardness testing and wear resistance testing. Microhardness testing: The microhardness of the cladding layer was tested using an HXD-1000TMS digital display microhardness tester with a load of 1.961 N and a holding time of 10 s. Wear resistance testing: The wear resistance of the cladding layer was tested using an MDW-02 friction and wear testing machine. The test was conducted at room temperature without lubrication. A Φ6mm YG8 cemented carbide ball was used as the friction pair, with a load of 15 N, a loading frequency of 3 Hz, a sliding stroke of 5 mm, and a friction time of 30 min.

[0050] The test results are shown in Table 1 and Figures 1 to 3 .

[0051] Table 1 Performance comparison of examples and comparative examples

[0052]

[0053] As shown in Table 1, the cladding layer containing 0% Y₂O₃ (Comparative Example 1) had an average friction coefficient of 0.5494, which was 3.06% higher than the substrate, and a weight loss of 1.8 mg, the same as the substrate. The cladding layer containing 1% Y₂O₃ (Example 1) had an average friction coefficient of 0.3974, which was 25.45% lower than the substrate; and a weight loss of 1.0 mg, which was 44.44% lower than the substrate. The cladding layer containing 3.5% Y₂O₃ (Example 3) had an average friction coefficient of 0.3847, which was 27.84% lower than the substrate; and a weight loss of 0.8 mg, which was 55.56% lower than the substrate.

[0054] Dye penetrant testing is used to detect cracks and pores on the surface of the coating. Figure 1 A comparison of Figures (a) and (b) shows that the addition of Y₂O₃ powder reduces the likelihood of coating cracking and also makes the coating surface smoother. Figure 1 As can be seen from Figures (c) and (d), under the premise of ensuring crack resistance, the present invention achieves the preparation of a thick coating on the surface of titanium alloy using the above-mentioned coating alloy material, and the thick coating can reach at least 10 mm.

[0055] Depend on Figure 2 It can be seen that the average microhardness of the cladding layer containing 0% Y2O3 (Comparative Example 1) is 425 HV. 0.2 The performance was improved by 32.81% compared to the substrate; the average microhardness of the cladding layer containing 1% Y2O3 (Example 1) was 495 HV. 0.2 The performance was improved by 54.69% compared to the substrate; the average microhardness of the cladding layer containing 3.5% Y2O3 (Example 3) was 526 HV. 0.2 This represents a 64.38% improvement over the substrate.

[0056] In this invention, a cladding layer with high hardness and high wear resistance is prepared. The substrate of the cladding powder is a Ti-6Al-4V homogeneous powder, which has good wettability, corrosion resistance, and high-temperature self-lubricating effect. It can improve the compatibility between the cladding layer and the substrate. The research direction has certain significance and good engineering application potential. WC has a similar coefficient of thermal expansion to TC4 alloy, high hardness, good thermal stability, and good wear resistance. Adding WC powder as a hard phase in the cladding layer can play a role in dispersion strengthening, enhancing the wear resistance of the cladding layer. Y2O3 has strong chemical activity and low electronegativity. Adding a certain amount of Y2O3 rare earth oxide to the cladding powder can, on the one hand, improve the absorption rate of the cladding powder to the laser, enhance convection and stirring inside the molten pool, reduce the large-scale agglomeration of the WC strengthening phase at the bottom of the cladding layer due to its high density, promote the uniform distribution of the WC strengthening phase in the cladding layer, and enhance the mechanical properties of the cladding material. On the other hand, Y2O3 rare earth oxide can eliminate pores in the cladding layer, refine grains, reduce residual stress and crack sensitivity of the cladding layer, and achieve large-thickness block deposition of the cladding layer.

[0057] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. Use of a TC4 clad alloy material that can be produced in large thickness dimensions, characterized in that, The application includes the following processing methods: S1. Pre-treat the surface of the titanium alloy to remove the surface oxide film and impurities; S2. Using coated alloy powder fed into a powder feeder, laser cladding is performed on the surface of titanium alloy to obtain a coating with a large thickness on the surface of titanium alloy, with a coating thickness of at least 3 mm. The cladding alloy material comprises the following 100% by weight percentages: 5-10% tungsten carbide powder, 1-4% yttrium oxide powder, and the balance being TC4 alloy powder; the tungsten carbide powder has a particle size of 15-53 μm, the yttrium oxide powder has a particle size of 10-50 μm, and the TC4 alloy powder has a particle size of 53-150 μm. The materials used in the coating alloy material are weighed according to the proportion and then ball-milled. After ball milling, the coating alloy powder is obtained by vacuum induction melting gas atomization. The ball mill operates at a speed of 100-300 rpm for 8-12 hours. During milling, the grinding balls and material are in an equal mass ratio, and milling is performed using alternating forward and reverse rotation, changing direction every 5-20 minutes. The vacuum induction melting gas atomization process is as follows: under the protection of argon gas with a purity of at least 4N, and with a vacuum degree not exceeding 5 × 10⁻⁶... -2 Under Pa conditions, the ball-milled material is heated to 1750-1850℃ and held for 20-30 minutes. During the heating and holding process, electromagnetic stirring is performed to form a molten liquid. The molten liquid is then atomized into powder under an atomizing gas pressure of 3-7 MPa. After cooling for 30-60 minutes, coated alloy powder is obtained in a powder collection tank and sieved to obtain coated alloy powder with a particle size of 53-75 μm. The laser cladding process parameters are as follows: laser power of 1.5-3.5kW, spot diameter of 3-5mm, defocusing amount of 15-30mm, scanning speed of 5-10mm / s, overlap rate of 30-50%, and powder feeding rate of 20-50g / min.

2. The application of the TC4 coated alloy material capable of producing large thicknesses according to claim 1, characterized in that, Use argon gas with a purity of at least 4N for protection, with a carrier gas flow rate of 1.5L / min, and perform laser cladding when the oxygen content in the inert gas chamber is below 100ppm.

Citation Information

Patent Citations

  • Preparation method of TC4 titanium alloy laser cladding reinforced coating

    CN107723703A

  • Rare earth oxide-containing laser repair layer on surface of titanium alloy and preparation method thereof

    CN111139467A